2019
DOI: 10.1111/omi.12275
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin gallate inhibits leukotoxin release by Aggregatibacter actinomycetemcomitans by promoting association with the bacterial membrane

Abstract: The oral pathogen, Aggregatibacter actinomycetemcomitans, produces a number of virulence factors, including a leukotoxin (LtxA), which specifically kills human white blood cells, to provide a colonization advantage to the bacterium. Strains of A. actinomycetemcomitans that produce more LtxA have been more closely linked to disease, indicating that this toxin plays a key role in pathogenesis of the bacterium. Disruption of the activity of LtxA thus represents a promising approach to reducing the pathogenicity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 58 publications
(82 reference statements)
0
7
0
Order By: Relevance
“…For example, plant materials may contain beneficial plant extracts that exert an anti-leukotoxic potential [ 32 , 33 , 34 , 35 ]. Recently, proanthocyanidins and epigallocatechin gallate of plant origin have been found to neutralize the effect of the A. actinomycetemcomitans leukotoxin [ 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, plant materials may contain beneficial plant extracts that exert an anti-leukotoxic potential [ 32 , 33 , 34 , 35 ]. Recently, proanthocyanidins and epigallocatechin gallate of plant origin have been found to neutralize the effect of the A. actinomycetemcomitans leukotoxin [ 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…We also observed that EGCg has large effects on LtxA release. When A. actinomycetemcomitans was treated with EGCg at a sub-inhibitory concentration (5 μg/mL), more LtxA was produced; however, most of the toxin remained in association with the bacterial cell surface rather than being secreted into the supernatant [ 44 , 45 ].…”
Section: Anti-virulence Properties Of Catechinsmentioning
confidence: 99%
“…The secondary structure of the toxin was dramatically altered in the presence of catechin gallates and resulted in inhibition of toxin binding to cholesterol, an important initial step in the cytotoxic mechanism. EGCg also reduces secretion of the toxin due to EGCg-mediated enhancement of LtxA affinity for the bacterial cell surface [71]. EGCg supressed the proliferation of vegetative B. cereus and B. subtilis but not the germination of spores of these bacteria [72].…”
Section: Non-lethal Effects On Bacterial Cellsmentioning
confidence: 99%